Development of North Tongauna Sub-District, Konawe Regency After Village Fund - Asriadi, Asriadi; Widayati, Weka; Alwi, La Ode (PT. Riset Press International, 2024)
The purpose of this study is to analyze and find out the development of the North Tongauna District after the existence of the Village Fund and the impact of the Village Fund on the village's original income in the North Tongauna District. Data analysis using the Klassen typology analyzes the development of the region. The results of the Village Fund analysis contribute to village original income obtained from BUMDes income in the villages of Waworoda Jaya, Sanuanggamo, Puundopi, Ambopi, Anggohu, Olua Ao, Nambeaboru, Barowila, Olo Onua and Andalambe where BUMDES is able to contribute to economic development in North Tongauna District. The results of the classification typology analysis Waworoda Jaya Village is in the relatively underdeveloped sector category so it is included in quadrant 4, Sanuanggamo Village is in the relatively underdeveloped sector category so it is entered in quadrant 4 Puundopi Village is in the relatively underdeveloped sector category so it is included in quadrant 4. Ambopi Village is in the potential sector category or can still develop so it is included in quadrant 3, Anggohu Village is in the relatively underdeveloped sector category so it is included in quadrant 4. Olua Ao Village is in the relatively underdeveloped sector category so that it is included in quadrant 4, Nam Village beaboru is in the relatively underdeveloped sector category so it is in quadrant 4. Barowila Village is in the potential sector category or can still develop so it is in quadrant 3, Olo Onua Village is in the relatively underdeveloped sector category so it is in quadrant 4, Andalambe Village is in the relatively underdeveloped sector category so it is in quadrant 4.